New foods - Marshall, Jared; Garner, Simon; Harding, Ben; Classroom Video (Australia : Classroom Video, 2006)
This program explore current trends in food and what influences the development of new food products. Meet food industry experts who discuss these current trends with particular focus on changes that chefs are making in restaurants and cafes, and foods styled for magazines
Title from title screen
Executive producer, Mark McAuliffe ; editor, Aaron Firth Donato ; sound, Alexy Gudimenko ; camera, Nick Hayward, Zane Lovitt, Jared Marshall
Voice over: Lisa Hickey
Featuring: Janine Allis...[et al.]
Keywords: Food -- Marketing; Food industry and trade; New products; Career education